Mutu Berbasis Green Education: Integrasi Prinsip Konservasi Lingkungan Dalam Standar Mutu Pendidikan Islam - Bahari, Denis; Aimah, Siti (Universitas Pakuan, 2026)
GREEN EDUCATION-BASED QUALITY: INTEGRATION OF ENVIRONMENTAL CONSERVATION PRINCIPLES IN ISLAMIC EDUCATION QUALITY STANDARDS This study aims to analyze the implementation of Green Education in improving the quality of Islamic education and examine the integration of religio-ecological values, such as amanah (trust), khalifah fil-ardh (vicegerent), and hifzh al-bi'ah (property), into educational quality standards. The study was conducted at Darussalam High School, which has a strong commitment to implementing a structured environmentally friendly program. A qualitative case study approach was used, with informants selected purposively, including the principal, teachers, environmental program coordinator, students, and school support staff. Data were collected through semi-structured interviews, observations, and document studies, then analyzed using the Miles and Huberman interactive data analysis model, encompassing data reduction, data presentation, and conclusion drawing/verification. The results indicate that the consistent implementation of a Green Education-based curriculum is able to foster an environmentally friendly school culture, increase student discipline, awareness, and responsibility, and strengthen the integration of religious values into environmental conservation practices. In the long term, Green Education shapes the ecological character of students with Islamic morals and a commitment to environmental sustainability. This research provides theoretical and practical contributions to the development of sustainability-based Islamic education quality standards.